Tuning hydrogen storage thermodynamic properties of ZrFe2 by partial substitution with rare earth element Y. (20th May 2021) - Qin, Changsheng; Wang, Hui; Liu, Jiangwen; Ouyang, Liuzhang; Zhu, Min
Abstract: ZrFe2 delivers the advantages of high hydrogen storage capacity and easy activation, but its de-/hydriding pressure is too high for practical application. In this work, we alloyed ZrFe2 with Y to obtain a single C15 Laves phase structure by the proper annealing process. The microstructure and hydrogen storage properties of Zr1- x Y x Fe2 ( x = 0.1–0.4) compounds were investigated. The results show that the cell volume increases and the dissociation pressure decreases with increasing Y content for the Zr–Y–Fe–H system. The Y alloying is beneficial for increasing hydrogen storage capacity despite the worsening plateau slope and hysteresis. The Zr0·6 Y0·4 Fe2 exhibits the highest hydrogen absorption capacity of 1.77 wt%, while the Zr0·8 Y0·2 Fe2 shows a dehydriding enthalpy of 25.06 kJ/mol H2 and dehydriding entropy of 116.53 J/mol·K H2, corresponding to the dissociation pressure of 59 atm at 298 K that is suitable for high-pressure hydrogen storage applications. Highlights: Rare earth element Y was alloyed with ZrFe2 . A single C15 Laves phase is obtained after annealing at 1473 K. The Y alloying increases the capacity and decreases the dissociation pressure. Zr0·8 Y0·2 Fe2 shows the best overall high-pressure hydrogen storage performance.